Lived Experiences of Primary Caregivers of Terminally Ill Persons - Orbe, Joyosthie B.; Matahari, Gabrielle H.; Castillo, Zajrel Wayne T. (8ISC Abstract Proceedings; 8ISC Abstract Proceedings, 2022)
Primary caregivers are highly affected in the care of the terminally ill, especially if they are immediate members of the family. This study explored the lived experiences of primary caregivers during and after the loss of family members with terminal illnesses. This qualitative, phenomenological study was conducted among sixteen participants, ages 20-80 years old, 16 informal caregivers of a terminally ill family member who passed away in a home-based setting not more than five years back. A self-constructed questionnaire was used to guide the face-to-face interviews with the respondents selected through purposive sampling and snowballing. The thematic analysis underwent the process of identification of patterns, data familiarization, coding, theme development, and revision. The findings of the study revealed holistic pain and time-management difficulty . Despite the satisfaction felt during the care, the results showed the primary caregivers lack of knowledge, overwhelming tasks, tiredness, anxiety, fear, financial strain for treatment and medications, and time management controversies , which negatively affected the caregivers’ life during their care of the terminally ill loved one. The lived experiences after losing the terminally ill loved ones resulted in sadness, dependence on God, relief, and a shift to diversional activities. The recommendation posits that primary caregivers must have support groups consisting of peers who have the same experience, understands the process, and are ready to help in times of need. Keywords : phenomenology, terminally ill, primary caregivers, lived experiences